2016
DOI: 10.3847/0004-6256/152/6/174
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Constraints on the Origin of Hot and Warm Jupiters With Close Friends

Abstract: Gas giants orbiting their host star within the ice line are thought to have migrated to their current locations from farther out. Here we consider the origin and dynamical evolution of observed Jupiters, focusing on hot and warm Jupiters with outer friends. We show that the majority of the observed Jupiter pairs (20 out of 24) are dynamically unstable if the inner planet is placed at 1 au distance from the stellar host. This finding is at odds with formation theories that invoke the migration of such planets … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…This result is similar to previous studies of high-e migration in stellar binaries (e.g. Petrovich & Tremaine 2016;Antonini et al 2016), and in multiplanet systems (Hamers et al 2016a). …”
Section: Hj Orbital Period Distributionsupporting
confidence: 92%
“…This result is similar to previous studies of high-e migration in stellar binaries (e.g. Petrovich & Tremaine 2016;Antonini et al 2016), and in multiplanet systems (Hamers et al 2016a). …”
Section: Hj Orbital Period Distributionsupporting
confidence: 92%
“…A similar issue has also been discussed for WJs with outer planetary-mass companions (Antonini et al 2016): the outer orbits in these systems, if primordial, are in most cases too small for the inner WJs to have migrated from 1 au. In addition, population synthesis simulations of high-eccentricity migration from 1 au, either via the companion on a wide orbit (Anderson et al 2016;Petrovich & Tremaine 2016) or secular chaos in multiple systems (Hamers et al 2017), have difficulty in producing a sufficient number of WJs relative to HJs.…”
Section: Implications For the In Situ Formation Scenariomentioning
confidence: 65%
“…Such a configuration is difficult to produce in a violent high-eccentricity migration scenario. Furthermore, Antonini et al (2016) examined the subset of observed WJs with characterized (in terms of mass, semimajor axis and eccentricity) external giant planet companions, and found that most systems are inconsistent with a 1 exoplanets.org, accessed July 4, 2019. 2 When dynamical (chaotic) tides are incorporated into the higheccentricity migration model, highly eccentric (e 0.9) WJs form rapidly, and subsequently circularize to become HJs .…”
Section: Introductionmentioning
confidence: 99%